(untitled) (Journal of the College of Basic Education, 2022)
The processes of evaluating kindergarten teacher preparation programs are of great importance, to ensure the quality and efficiency of the educational process and in order to be in line with modern trends, and that this evaluation begins by revealing the strengths and weaknesses of the preparation programs. The current research aims to reveal the strengths and weaknesses of the program Preparing kindergarten students, and this is the first goal. The current research was determined by the students of the fourth stage of the kindergarten department in the College of Basic Education / Al-Mustansiriya University for the academic year 2013-2014. The researchers used the analytical descriptive research method, and the researchers chose, in a simple random way, (76) female students from the fourth stage.